Renal Capillary Hemangioma Mimicking Urothelial Carcinoma, A Case Report and Review of the Literature - Bita Geramizadeh; Nadereh Shams; Pouya Iranpour; Mohammad javad Rajabi (Iranian Society of Pathology, 2019)
Renal hemangioma is a rare tumor which can be capillary or cavernous. There have been less than 30 renal capillary hemangioma cases reported in the English literature. Herein we will report a case of renal hemangioma which was detected in a 74-year-old man operated with the impression of urothelial carcinoma of hilum.